2005
DOI: 10.1007/s00284-005-0020-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Commensal Bacteria from Umbilical Cord Blood of Healthy Neonates Born by Cesarean Section

Abstract: In a previous study, lactic acid bacteria were isolated from meconium obtained from healthy neonates born by cesarean section. Such a finding suggested that term fetuses are not completely sterile, and that a mother-to-child efflux of commensal bacteria may exist. Therefore, presence of such bacteria in umbilical cord blood of healthy neonates born by elective cesarean section was investigated. The blood samples were submitted to an enrichment step and then inoculated onto agar plates. All the identified isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
424
5
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 583 publications
(478 citation statements)
references
References 21 publications
9
424
5
19
Order By: Relevance
“…However, microbial colonization of the human infant may begin earlier. The dogma of sterile intrauterine environment has recently been challenged by reports on detection of diverse microbes in placenta, umbilical cord, amniotic fluid, and meconium (3)(4)(5)(6)(7)(8)(9)(10). Taking these preliminary observations together, the contact with the complex bacterial communities is clearly already initiated in utero and the impact of maternal microbiota may be more important than we had previously believed.…”
Section: Microbial Exposure In Uteromentioning
confidence: 90%
See 1 more Smart Citation
“…However, microbial colonization of the human infant may begin earlier. The dogma of sterile intrauterine environment has recently been challenged by reports on detection of diverse microbes in placenta, umbilical cord, amniotic fluid, and meconium (3)(4)(5)(6)(7)(8)(9)(10). Taking these preliminary observations together, the contact with the complex bacterial communities is clearly already initiated in utero and the impact of maternal microbiota may be more important than we had previously believed.…”
Section: Microbial Exposure In Uteromentioning
confidence: 90%
“…Experimental evidence in mice has been reported to support this notion (12,13). Maternal bacteria present in blood would reach the placenta tissue, from which microbes could reach the amniotic fluid and be swallowed by the fetus (3,4,8) or transfer into the fetal circulation, as has been demonstrated from maternal cells (14) and fetal transfer DNA material to maternal serum (15). The translocation of commensal bacteria from the mother to the fetus and neonate has been reported to have a variety of routes, for example, through the mesenteric lymph nodes, breast tissue, and skin.…”
Section: Microbial Exposure In Uteromentioning
confidence: 97%
“…However, recently, several studies have shown the presence of diverse microbes in placenta, umbilical cord, amniotic fluid, and meconium [12,13]. The colonization of gut microbiota can be influenced by several factors such as mode of delivery, breast feeding, diet, antibiotics and life style [14].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…The presence of specific strains of maternal enteric bacteria in the meconium implies that the fetus is exposed to microbes from the maternal gut in utero (74) and points to the maternal gut as a key player in the development of fetal gut microbiome. Commensal bacteria from the maternal gut have been isolated from umbilical cord blood of healthy neonates born by cesarean section (71) and oral bacteria have been found in the placenta and amniotic fluid (71) in healthy term pregnancies, and likely unrelated to intra-amniotic infection and preterm labor (69,75). It is possible that maternal gut dysbiosis as a result of obesity, poor nutrition, or even stress, could ultimately affect the microbes the fetus is exposed to in utero, and may serve to alter fetal gut development.…”
Section: Fetal Gut Microbiome Acquisition In Uteromentioning
confidence: 99%